(untitled) (Studia Prawnicze / The Legal Studies, 2017)
Znaczenie Karty praw podstawowych Unii Europejskiej (dalej powoływana w tekście jako: Karta) dla kształtowania prawa Unii Europejskiej oraz jej oddziaływanie na prawo krajowe państw członkowskich jest przedmiotem stałego zainteresowania polskiej nauki prawa. Z tego względu celem poniższych rozważań nie jest przeprowadzenie analizy stosowania Karty w krajowym porządku prawnym w ogólności, lecz przedstawienie stanowiska Trybunału Sprawiedliwośc Unii Europejskiej w odniesieniu do jej oddziaływania w kontekście stosowania prawa karnego państw członkowskich. Przedmiotem analiz będą zatem kwestie dotyczące tej sfery prawa, w której państwa członkowskie – stanowiąc i stosując prawo – korzystają z przysługujących im kompetencji do karania (ius puniendi). The article focuses on the recent jurisprudence of the Court of Justice of the European Union in the context of the national criminal laws of the Member States, concerning the scope of application of the Charter. Drawing conclusions from this jurisprudence the Author answers the question when the Member State is ’implementing Union law’ in the meaning of Article 51(1) of the Charter in the criminal law context. It is considered that Member States implement Union law when interpreting framework decisions (Lanigan, JZ, Vilkas), when assessing the conformity of the national measures with framework decisions (Jeremy F., Radu), when executing judgements in the framework of the mutual recognition (Aranyosi and Caldararu) and when assuring the effectiveness of EU law by enacting criminal sanctions (Tarrico). In addition, in some situations Member States may be considered to be implementing Union law while enacting national measures which may affect the rights derived from Union law (Delvigne). It is assumed in the article that CJEU is often called to strike the fair balance between the different (and sometimes diverging) interests of three categories of actors: interests of individuals (to have their fundamental rights protected), interests of Member States (to exercise ius puniendi) and interests of the European Union as a whole (to ensure effectivess of EU law).